Ιnfluence of increased dietary valine on broiler performance, serum components, nitrogen excretion and jejunum histomorphology - Gül, ET; Yıldız, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Current experiment was carried out to examine the effects of increasing valine levels in broiler diets based on corn-soybean meal on performance, slaughtering and serum parameters, nitrogen excretion, and jejunum histomorphology. A total of 480 male broiler chicks were randomly allocated to six treatment groups with eight replications, each containing 10 birds. In the three-period experiment, basal diets were prepared according to the needs of broilers and valine levels were determined as 100% (V100, control), 110% (V110), 120% (V120), 130% (V130), 140% (V140), and 150% (V150). The performance parameters were not affected in the first period, and best results were obtained in V120 group in the second period and cumulatively. Among the slaughtering characteristics, relative thigh+drumstick weight linearly increased and breast weight decreased. The glucose, total protein, globülin, and creatinine linearly increased, while triglyceride decreased quadratically. Nitrogen excretion decreased linearly with increasing dietary valine. In addition, highest villus height was obtained in V130 and best villus surface area was obtained in V120, while crypt depth was negatively affected by increasing valine. According to results, highest performance and villus surface area were obtained in V120 group. The high levels administration of valine (140 and 150%) adversely affected relative breast weight and jejunum histomorphology, but nitrogen excreted with feces decreased. Therefore, valine level in broiler diets can be increased by 20% of the recommended level.